Impact of Covid-19 Lockdown on Sleep-Wake Schedule and Associated Lifestyle Related Behavior: A National Survey - Sinha, Meenakshi; Pande, Babita; Sinha, Ramanjan (Journal of public health research, 2020)
Background: Lockdowns to prevent the community transmission of COVID-19 pandemic has confined the people at home and imposed social restrictions, which is expected to cause alterations in circadian driven sleep-wake schedule and its associated lifestyle behaviors. Design and Methods: An online questionnaire-based survey was conducted to assess the impact of lockdown on the sleepwake pattern, meal timings and digital media exposure time on the Indian population during lockdown. Responses of 1511 participants (age ≥18 years) were analyzed to assess the effect of gender and age on these parameters before and during lockdown. Results: The sleep onset-wakeup times and meals’ time was significantly delayed during lockdown, which was more pronounced in younger subjects. However, young individuals reported increased sleep duration at this time. Increased digital media duration was evident in all age groups, mainly in males. However, females reported more delay in sleep onset-waking time and first meal timing with longer sleep duration during lockdown. Conclusions: Discord with social and natural cues due to complete lockdown during COVID-19 pandemic leads to a state of social jetlag with delayed sleep-wake, meal timings and excessive digital media exposure among Indians, which has differential impact on males and females as well as across different age groups. These findings have applied implications in sleep health and related behavior during longer social isolation conditions such as current COVID-19 or similar situations and may help to prepare better for any such future events. Significance for public health In the background of ongoing COVID-19 pandemic, and increased incidences of domestic violence and unrest, this study reflects a significant influence of prolonged lockdown on some of the basic indicators of lifestyle such as sleep-wakefulness, timing of meals and usage of electronic media. Increased sleep duration in younger age groups with increased screen time and delayed meal time indicate their increased susceptibility to stress and its psychological consequences such as depression, thereby potentially affecting professional productivity and personal relationships. The senior age groups are also adversely affected in relation to these aspects, being increasingly susceptible to associated health risks. On the other hand, across genders, women exhibit greater disruption of their lifestyle behavior in terms of sleep-wake pattern and meal timings which might lead to hormonal imbalance related health conditions over long time. These findings hold vital potential to mitigate any such associated adverse effects.